The Worthiness of Adobe Flash Multimedia in Grading Course‘s Fashion Design Program of Malang State University (Research, Society and Development, 2019)
The used of Adobe Flash Multimedia as learning media is considered to be less used by the teachers or lecturer in learning process. In fashion design program, especially in grading course, Adobe Flash Multimedia is applied in the learning process. Thus, the objective of this study is tried to view the worthiness of Adobe Flash multimedia in grading subjects in fashion design program, Malang State University. The population is involving the students who has obtained grading subject. By using media worthiness pattern, the result shows that Adobe Flash multimedia in grading subjects in fashion design program is worthy to use in learning subject in Malang State University from media and materials expert, and also students. It is hoped that this multimedia can ease in the learning process and increase learning media to be more interesting and encourage motivation study.